Influence of humidity on the resistive switching of hexagonal boron nitride-based memristors - Lukas Völkel; Rana Walied Ahmad; Alana Bestaeva; Dennis Braun; Sofia Cruces; Jimin Lee; Sergej Pasko; Simonas Krotkus; Michael Heuken; Stephan Menzel; Max C. Lemme (npj 2D Materials and Applications)
Abstract Two-dimensional material-based memristors have recently gained attention as components of future neuromorphic computing concepts. However, their surrounding atmosphere can influence their behavior. In this work, we investigate the resistive switching behavior of hexagonal boron nitride-based memristors with active nickel electrodes under vacuum conditions. Our cells exhibit repeatable, bipolar, nonvolatile switching under voltage stress after initial forming, with a switching window >103 under ambient conditions. However, in a vacuum, the forming is suppressed, and hence, no switching is observed. Compact model simulations can reproduce the set kinetics of our cells under ambient conditions and predict highly suppressed resistive switching in a water-deficient environment, supporting the experimental results. Our findings have important implications for the application of h-BN-based memristors with electrochemically active electrodes, since semiconductor chips are typically processed under high vacuum conditions and encapsulated to protect them from atmospheric influences.